Aging drives organ‐specific alterations of the inflammatory microenvironment guided by immunomodulatory mediators in mice. Issue 5 (14th April 2021) - Schädel, Patrick; Troisi, Fabiana; Czapka, Anna; Gebert, Nadja; Pace, Simona; Ori, Alessandro; Werz, Oliver
Abstract: Aging is accompanied by chronic, low‐grade systemic inflammation, termed inflammaging, a main driver of age‐associated diseases. Such sterile inflammation is typically characterized by elevated levels of pro‐inflammatory mediators, such as cytokines, chemokines and reactive oxygen species causing organ damage. Lipid mediators play important roles in the fine‐tuning of both the promotion and the resolution of inflammation. Yet, it remains unclear how lipid mediators fit within the concept of inflammaging and how their biosynthesis and function is affected by aging. Here, we provide comprehensive signature profiles of inflammatory markers in organs afflicted with inflammation of young and old C57BL/6 mice. We reveal an organ‐specific footprint of inflammation‐related cytokines, chemokines and lipid mediators, which are distinctively affected by aging. While some organs are characterized by a pronounced pro‐inflammatory microenvironment and impaired resolution during aging, others display elevated levels of pro‐resolving mediators or an overall decrease in inflammatory signaling. Our results demonstrate that it proves difficult to establish a unifying concept for alterations of immunomodulatory mediators as consequence of aging and that organ specificity needs to be considered. Moreover, our data imply that inclusion of lipid mediators into the concept of inflammaging provides a comprehensive tool to characterize the inflammatory microenvironment during aging on a broader and yet, more detailed scope.